2019
DOI: 10.1098/rsif.2019.0389
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling identifies the role of adaptive immunity as a key controller of respiratory syncytial virus in cotton rats

Abstract: Respiratory syncytial virus (RSV) is a common virus that can have varying effects ranging from mild cold-like symptoms to mortality depending on the age and immune status of the individual. We combined mathematical modelling using ordinary differential equations (ODEs) with measurement of RSV infection kinetics in primary well-differentiated human bronchial epithelial cultures in vitro and in immunocompetent and immunosuppressed cotton rats to glean mechanistic details that underlie RSV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 56 publications
(157 reference statements)
0
21
0
Order By: Relevance
“…We attempt to determine which of these scenarios is occurring through the use of mathematical models. Mathematical models have long been used to improve our understanding of respiratory viral infections 25 and to study different aspects of within-host dynamics of viral infections, such as drug treatment 26,27 and resistance, [28][29][30] the role of the immune response, 31,32 and coinfections. [33][34][35] Our previous study using mathematical models of coinfections indicated that viruses with a faster growth rate will suppress viruses with a slower growth rate, 33 a dynamic that might provide insight into SARS-CoV-2 coinfections with other respiratory viruses.…”
Section: Introductionmentioning
confidence: 99%
“…We attempt to determine which of these scenarios is occurring through the use of mathematical models. Mathematical models have long been used to improve our understanding of respiratory viral infections 25 and to study different aspects of within-host dynamics of viral infections, such as drug treatment 26,27 and resistance, [28][29][30] the role of the immune response, 31,32 and coinfections. [33][34][35] Our previous study using mathematical models of coinfections indicated that viruses with a faster growth rate will suppress viruses with a slower growth rate, 33 a dynamic that might provide insight into SARS-CoV-2 coinfections with other respiratory viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Inbred male and female cotton rats (Sigmodon hispidus) were purchased from Envigo (Indianapolis, Indiana) and housed as previously described [ 32 , 33 ] in polysulfone microisolation cages (NextGen Rat 900, Allentown Inc., Allentown, NJ, USA) in a barrier facility with a 12:12 hour light cycle. Cotton rats were maintained at 20 ± 2°C and 30% to 70% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Stocks of RSV A2 were grown in human epithelial (HEp2) cells as described [ 32 , 33 ]. HEp2 cells were infected with an MOI of 0.001 of RSV A2 in MEM for 1 hour at 37°C and incubated in 30 mL MEM/2% fetal calf serum at 37°C for 4 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we analyzed the differences in airway resistance, tissue damping and pulmonary compliance in RSV infected female and male cotton rats. We compared pulmonary function at 4 days post-RSV infection since this is the time point in which there is peak viral replication in the lungs of cotton rats [46].…”
Section: Female and Not Male Cotton Rats Demonstrated Perturbationsmentioning
confidence: 99%